Justice in the Name of Six Million Accusers: the Case of the Attorney General of the Government of Israel v. Adolf Eichmann in the Context of International Law - N. A. Safarov (Московский журнал международного права, 2022)
INTRODUCTION. The legal saga of the prosecution of Adolf Eichmann, one of the most wanted war criminals and chief “architect” of the Holocaust, raises many ethical, political and legal problems. The Eichmann trial is unprecedented in the long history of international criminal law for many reasons. Although many leaders of Nazi regime were put on trial at Nuremberg before International Military Tribunal, mass killings and other outrageous crimes against Jews was not the main object of the trial. Thereby prosecution and punishment one of the most important organizers of the genocide of Jewish people, creator of new type of evil and new type of crime, become the great task of the State of Israel.MATERIALS AND METHODS. The theoretical basis of the study consists of the works of leading international lawyers specializing in international criminal law, as well as the international extradition of criminals; the analytical base comprises of the decisions of the Nuremberg International Military Tribunal, as well as the national courts of the State of Israel, in particular the cult decision the Attorney General of the Government of Israel v. Adolf Eichmann, as well as the decisions of the national courts of the United States, cited in the article for the purpose of comparative analysis. The methodological basis of the research comprises historical method, methods of formal logic, including analysis, synthesis and analogy, as well as systemic, comparative legal methods and method of interpretation.RESEARCH RESULTS. Based on the study of international legal instruments and international judicial practice, as well as the national legislation of the State of Israel, the author made conclusions related to the abduction of accused from the territory of a foreign state, in particular its consequences in the form of violation of the sovereignty of the state. At the same time, the article contains a statement that the unlawfulness of the arrest does not prevent the court from exercising jurisdiction over the person. In the context of the administration of justice by the State of Israel, the author analyzes the Convention relating to the Status of Refugees of December 14, 1951, paying special attention to the problem of the possible immunity of the accused based on the refugee status granted by the state.DISCUSSION AND CONCLUSIONS. In the course of the study, the author analyzed a significant amount of materials, summarized the doctrinal positions put forward by a number of prominent international scholars, and also formed the conclusion that the trial of Eichmann marked not only the administration of justice over the international criminal, but also provided another opportunity for a broad international publicity of the horrors of the Nazi regime and the need to unite collective efforts of states to save future generations from such international crimes.